A closer look at attachment, sexuality, and couple relationships. (April 2020) - Busby, Dean M.; Hanna-Walker, Veronica; Yorgason, Jeremy B.
In this study, the relationships between attachment patterns and relationship outcomes were explored through the mechanism of sexuality with two large samples from the U.S. In the first sample ( N = 4, 834), the associations between insecure attachment patterns, the number of committed and casual sexual partners, timing of sexual debut, and relationship status were explored. In the second sample, a nationally representative sample of recently married couples ( N = 4212), an actor–partner model was used to explore the associations with attachment on the number of sexual partners and sexual timing and their subsequent influence on relationship and sexual satisfaction over two time points. The results indicated that, for Sample 1, insecure attachment was associated with both the number of casual and committed sexual partners and an increased likelihood of being single for men and women. For Sample 2, the actor–partner measures of attachment were associated with relationship and sexual satisfaction over two time points but had weak associations with the number of sexual partners and sexual timing.